Effect of hepatitis B virus (HBV) infection on the course of pregnancy and newborns’ health status - Łapiński, Tadeusz; Stepaniuk, Julita; Tomasiewicz, Krzysztof; Lebensztejn, Dariusz; Kulikowski, Marek; Flisiak, Robert (Clinical and Experimental Hepatology, 2015)
Introduction: The effect of chronic hepatitis B virus (HBV) infection on pregnancy is not clear. Hepatitis B virus infection of newborns in the case of natural delivery occurs in 70-90% of cases. Risk factors of infection are the presence of serum HBeAg and HBV DNA level above 107 IU/ml. Active and passive prevention protect more than 95% of neonates born to mothers infected with HBV. The aim of the study was to determine the course of pregnancy in HBV-infected women, the mode of delivery, efficacy of prophylaxis against HBV infection in newborns, and health condition of newborns within the first years of life. Material and methods: The course of 104 pregnancies in 69 women infected with HBV was monitored. Hepatitis B virus viral load was determined by PCR using the AmpliPre/COBAS TaqMan HBV system. Neonatal HBV infection and the health condition at birth and during the first year of life were analyzed. Results : All included pregnant women were HBeAg negative. No clinically significant disorders were observed during pregnancy. Viral load measured in the third trimester did not exceed 107 IU/ml in any pregnant woman. Only 5 (8%) of them demonstrated levels above 105 IU/ml. Two women (1.9%) experienced a miscarriage, which was considered as not associated with HBV infection. The majority (56%) of pregnancies ended with spontaneous labor. Complete prevention against HBV was applied in 79% of newborns. Hepatitis B virus infection was diagnosed in 3 children who received incomplete or no prophylaxis. Hepatitis B virus infection occurred in 3 (2.9%) children born naturally, who did not receive proper prevention after delivery. The Apgar score in children born to mothers infected with HBV did not differ significantly from that in neonates born to healthy women from the same population. Allergic disorders developed in 17 children who underwent HBV prophylaxis. Conclusions : Low viral load in pregnant women infected with HBV and the absence of HBeAg reduce the probability of infection of newborns. Proper prevention carried out after delivery seems to be the most important method to prevent HBV infection in newborns.